Neural Correlates of Autistic Traits in the General Population: Insights Into Autism. - Kennedy, Daniel P. (American Journal of Psychiatry, 2009)
A commentary on an article by Adriana Di Martino et al. that appeared in this issue on pp. 891–899. In their article, Di Martino et al., in a study of autism, found that the degree of autistic traits in an individual is linked to a functional relationship between two particular regions of the brain, that is, the pregenual anterior cingulate and the anterior mid-insula. The writer suggests that although it has yet to be seen whether or not the particular brain circuitry identified by Di Martino et al. is altered in individuals diagnosed with autism, future research into brain-behavior relationships using increasingly sophisticated behavioral measures will surely assist in informing biological models of brain organization and brain development in autism.